Study on water quality of the Pahang river, Malaysia - Hou, Chenxiao (2014)
From now on, the Ecological status of Malaysia is not bad with other countries, because many developing nations have same situation with Malaysia. Even though the government set up the Environmental Quality Act (EQA) in 1974, the water quality of the Malaysia still Worsening, especially the inland rivers. The main pollution is from point and non-point source in the river, department of environment can controlled the point sources, there are lots of the point sources from the runoff and sullage. However, the government can take the steps which are used before to control the non-point source pollution and untreated sullage which are main factor on the status in the river. The objectives of study were To determine the water quality status of the Pahang River based on water quality index (WQI) and To obtain the factors that affected the water quality at the Pahang River. There are two types of test was performed in this study, which are site visit and experiment in laboratory. For in-situ test, the tests are PH, Turbidity, ammonia nitrogen, biochemical oxygen demand, and dissolved oxygen, chemical oxygen demand, suspended solid ate the tests that was been carried out in the laboratory. From the results: AN (0.09-0.204mg/L), BOD (3.2-6.2mg/L), COD(22-50mg/L), DO(3.64.63mg/L), Turbidity(22-66 NTU), Temperature(29-30°C ), TSS (11-102 mg/L), pH(6.7-7.82).in the conclusion One of the main pollutants which are ammoniac nitrogen (NH3-N) has been identified by the department of environment. But the new regulation show that sewage and industrial set allowable NH3-N concentration quite high (5mg/L), so many result got lower value in the water quality index for the river. The water quality can be affect by the forest, human activities and construction sit.